Diagnostic and clinical characteristics of early‐manifesting females with Duchenne or Becker muscular dystrophy. Issue 11 (14th August 2014) - Imbornoni, Lauren; Price, Elinora T.; Andrews, Jennifer; Meaney, F. John; Ciafaloni, Emma; Cunniff, Christopher
<x xml:space="preserve">Abstract</x> Manifestations of Duchenne and Becker muscular dystrophy (DBMD) are present in up to 40% of heterozygous females, but there are few reports of females who exhibit skeletal muscle symptoms in childhood. From the Muscular Dystrophy Surveillance Tracking and Research Network, a multi‐site population‐based surveillance network for dystrophinopathy, nine symptomatic female heterozygotes with onset of symptoms prior to age 9 years were identified. The median age at diagnosis was 8.3 years, and the median interval from first symptoms to diagnosis was 1.35 years. Of the nine female heterozygotes, four had a positive family history, seven had intellectual disability and five had at least one mental health disorder. Mental health concerns included attention deficit hyperactivity disorder (ADHD), autism spectrum features, bipolar disorder, and depression. The frequency of intellectual and mental health problems in this group is higher than previously reported for affected males and for symptomatic females. These findings may have implications for diagnosis of early manifesting heterozygotes and for their health supervision. © 2014 Wiley Periodicals, Inc.